Clinical case formulation : varieties of approaches - Sturmey, Peter; Wiley InterScience (Online service) (Chichester, UK ; Malden, MA : John Wiley & Sons, 2009)
Case formulation is a key skill for mental health practitioners, and this book provides examples of ten case formulations representing the most common mental health problems in a variety of populations and contexts, offering commentary on contrasting formulations of the same case.: Provides an overview of the general features of case formulation and how it can drive treatment; Features clinical cases from a variety of populations, focusing on a range of different problems; Covers all the major theoretical perspectives in clinical practice - behavioural, cognitive behavioural, psychodynamic, me.
Case formulation: a review and overview of this volume / Peter Sturmey -- Sally : a case of depression / Mari E Brannigan and Christopher Williams -- Cognitive formulation of depression : case of Sally / Cory F. Newman -- Behavioural formulation of depression : the case of Sally / C.W. Lejuez, Tyish Hall Brown, & Derek R. Hopko -- Commentary on cognitive and behavioural formulations of anxiety-depression / Christopher J. Williams -- Zeppi : a case of psychosis / Anthony DiMech, David Kingdom, and Maged Swelam -- A psychiatric approach to case formulation / David A. Casey -- A behavior analytic formulation of a case of psychosis / David A. Wilder -- Formulating Zeppi : a commentary / Richard Bentall -- A case of eating disorder : Antoinette Hilbert-Smith / J. Tim Newton -- A formulation of the case of Antoinette : a multiperspective approach / Priyanthy Weerasekera -- The functional analysis and functional analytic clinical case formulation : a case of anorexia nervosa / Raimo Lappalainen, Tero Timonen and Stephen N. Haynes -- Commentary on formulations of eating disorders / Myra Cooper -- A case of problematic behavior in an older adult / Helen DeVries -- A cognitive analytic formulation / Mark Dunn -- The core conflictual relationship theme : a psychodynamic formulation of the case of Mrs. Lewis / Marna S. Barrett -- Commentary on formulations of a case of problematic behavior in an older adult / Kevin Howells and Laurence Jones -- A case of anger in a person with intellectual disabilities / Betsey A. Benson -- A psychodynamic formulation / Nigel Beail and Tom Jackson -- A cognitive-behavioural formulation of anger in a man with an intellectual disability / Paul Willner -- Commentary on formulations of anger in a person with intellectual disabilities / Robert Didden -- Contemporary themes in case formulation / Tracey Eells.
Includes bibliographical references and index.
Print version record.
Keywords: Clinical psychology -- Methodology; Counseling -- Case studies; Psychotherapy -- Practice; MEDICAL -- Psychiatry -- General; PSYCHOLOGY -- Psychopathology -- General; PSYCHOLOGY -- Clinical Psychology; PSYCHOLOGY -- Mental Illness; MEDICAL -- Mental Health; Clinical psychology -- Methodology; Counseling; Psychotherapy -- Practice; Psychology, Clinical -- methods; Mental disorders -- Diagnosis; Mental disorders -- Therapy; Psychotherapy -- methods; Electronic books; Case studies; Electronic books